Achieving Goals in Type C Terminal Services at Porong Terminal - Siti Eka Novi; Isnaini Rodiyah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effectiveness of Type C Terminal services in Porong District, Sidoarjo Regency and the factors that affect Type C Terminal services at Porong Terminal. The type of research is descriptive qualitative research. Data collection techniques were carried out through observation, interviews and documentation. Determination of informants in this study using purposive sampling technique. Data analysis was carried out with data collection techniques, data reduction, data presentation, and then drawing conclusions. The results of this study indicate that the effectiveness of Type C terminal services at Porong Terminal, namely; The achievement of the target is in accordance with the service SOP that has been achieved and has been carried out at the Porong Terminal, the achievement of existing facilities and infrastructure is lacking and needs to be addressed again. Adaptability shows the way that interaction or communication is carried out as needed and carried out based on orders, both direct communication. Job satisfaction shows that the organization must provide motivation and direction first, trying to provide passenger comfort. Responsibility shows that employees and their duties and authorities follow the rules and have been divided according to their respective duties. And the factors that affect each personnel are also divided according to their respective responsibilities with the condition of the Type C Terminal at Porong Terminal, good facilities and infrastructure at Porong Terminal but also there are still many things that need improvement because they are not feasible and the facilities are inadequate. need to be built.